The Evolution of the Belt and Road Trade Network and Its Determinant Factors. Issue 14 (14th November 2019) - Chong, Zhaohui; Qin, Chenglin; Pan, Su
ABSTRACT: This study reveals the evolution of the Belt and Road trade network, and discusses the determinant factors of trade relationships by employing network analysis methods. Using 65 countries' trade flow data in 2012, 2014, and 2016, the network indices show that the Belt and Road initiative has improved trade network's connectivity significantly. The results of blockmodels show that the trade network can be partitioned into four blocks, including " Dominators, " " Brokers, " " Generators, " and " Receivers ." Furthermore, the spatial proximity, cultural differences, trade agreements, economic distance, and trade facilitations have significant impacts on the formation of trade network according to the QAP model.